Re-Do: Performance-rester - Schneider, Rebecca; D, Solveig (Peripeti, 2010)
Rebecca Schneider’s essay “Re-Do: Performance Remains” constitutes one of several versions circulating in academia of Schneider’s ‘original’ essay “Performance Remains”, first printed in Performance Research in 2001. The author kindly permitted Peripeti to print a translation of this specific version of the essay. The circulation of different versions of ’the same’ text is significant, since Schneider in this essay precisely deconstructs the conventional dichotomy between stable documents and ephemeral performances. Not only does the history of the essay itself testify to the fact that texts and other documents are heir to the same flaws and transformations as oral and performative manifestations, but more importantly, Schneider wants to draw attention to the documentary and archival aspects of performance itself, as it is expressed for example in oral traditions and historical re-enactments, in which another kind of historical knowledge is transmitted than the one based on artifacts and documents.